2011
DOI: 10.1007/s10508-011-9865-7
|View full text |Cite
|
Sign up to set email alerts
|

Latent Structures of Female Sexual Functioning

Abstract: For the last three decades, male and female sexual responses have been conceptualized as similar, based on separated and sequential phases as proposed by the models of Masters and Johnson (1966) and Kaplan (1979) model. However, there is a growing debate around the need to conceptualize female sexual response and the classification of sexual dysfunction in women, in view of the upcoming editions of the DSM and ICD. The aim of this study was to test, using structural equation modeling, five conceptual, alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
(70 reference statements)
1
13
0
2
Order By: Relevance
“…Kaplan even describes it as «phobic avoidance» [6]. Carvalho et al, after testing five alternative models of female sexual function, concluded that the diagnoses vaginismus and dyspareunia overlapped to a great degree [19]. One consequence of the collapse of the two diagnoses is male dyspareunia which, because it was deemed exceedingly rare, was scrapped completely from the nomenclature [20].…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan even describes it as «phobic avoidance» [6]. Carvalho et al, after testing five alternative models of female sexual function, concluded that the diagnoses vaginismus and dyspareunia overlapped to a great degree [19]. One consequence of the collapse of the two diagnoses is male dyspareunia which, because it was deemed exceedingly rare, was scrapped completely from the nomenclature [20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, within the literature more broadly, the results of some factor analytic studies suggest that there may in fact be similarities between men and women who experience low sexual function, and between men and women who do not. The sexual response cycle has been found to have distinct desire, arousal, and orgasm phases for men and women without low sexual function (Carvalho, Vieria & Nobre, 2011; Giles & McCabe, 2009), whereas sexual desire, arousal, and orgasm tend to overlap for men and women experiencing low sexual function (Carvalho, Vieira & Nobre, 2012; Carvalho et al, 2011; Corona et al, 2015; Giles & McCabe, 2009). These findings are consistent with the notion of higher symptom severity being associated with greater comorbidity (Kessler et al, 2005; Krueger, 1999), and with the similar dimensional findings for men and women across Forbes et al’s (2015a, 2015b) later studies in particular.…”
Section: Part 3: Studies That Have Tested the Hypothesis That Sexual mentioning
confidence: 99%
“…This is important because sexual function is continuous (i.e., it does not naturally separate into discrete categories of ‘function’ and ‘dysfunction’), and phases of sexual response often overlap (Carvalho et al, 2012; Carvalho et al, 2011; Corona et al, 2015; Giles & McCabe, 2009). In contrast, the DSM deems sexual dysfunctions as either present or absent, and implies that low levels of arousal (e.g., Female Sexual Interest/Arousal Disorder, or Erectile Disorder) are categorically distinct from orgasmic function (e.g., Female Orgasmic Disorder, Premature [Early] Ejaculation, or Delayed Ejaculation).…”
Section: Part 4: Implications and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Edition des Diagnostischen und Statistischen Manuals Psychischer Störungen (DSM-5) und vereint die revidierten Diagnosen von Dyspareunie und Vaginismus. Die Zusammenführung beider Störungsbilder in der GPSPS-Diagnose resultierte aus großen Überschneidungen der Symptombilder und Schwierigkeiten ihrer differenzialdiagnostischen Abgrenzung [Carvalho et al, 2012].…”
Section: Introductionunclassified